Isolation of nanocrystalline cellulose from oil palm empty fruit bunch – a response surface methodology study - Song, Yee Kai; Chew, Irene Mei Leng; Choong, Thomas Shean Yaw; Tan, Jully; Tan, Khang Wei (EDP Sciences, 2016)
The research work studied the extraction of Nano Crystalline Cellulose (NCC) from oil palm empty fruit bunch (EFB), with aid of Response Surface Methodology (RSM). Particle size analysis using Malvern Zetasizer had confirmed the extracted NCC fall within the desired nano scaled range. The impact of three input parameters, namely concentration of NaOH solution during alkaline treatment, concentration of H2SO4 solution during acid hydrolysis, and duration for acid hydrolysis on NCC particle were investigated. From ANOVA study, it had suggested that the current RSM model is significant to interpret the interaction among the all three input parameters.